A Comprehensive Review on Thermal Radiation of Open Cellular Porous Materials - Khantikomol, P.; Krittacom, B. (Naresuan University Engineering Journal, 2014)
The radiative heat transfer in highly porous materials, open cellular structure or open-celled foam, is reviewed to characterize the radiative transport process in terms of fundamental radiative properties such as extinction coefficient (β), albedo (ω) and scattering phase function :P(cosq). Firstly, the geometric shape and topology of open-celled foam are deeply presented. Thereafter, the governing equation for radiative transfer (RTE) and the solution methods are represented. Finally, analytical expressions relating such radiative properties to basic structural parameters developed through mathematical modeling and experimental studies are briefly recalled and discussed.